Efficacy of Quinone outside inhibitor (QoI) and de-methylation inhibitor (DMI) fungicides against grape anthracnose - INDU S. SAWANT* and S.D. SAWANT, DINESH S. SHETTY, SHUBHANGI P. NARKAR, (Indian Phytopathology, 2014)
Studies were conducted during 2010-11 monsoon season to evaluate the efficacy of fungicides belonging to QoI and DMI groups in controlling anthracnose disease in vineyard at the National Research Centre for Grapes, Pune. Commercial formulations of azoxystrobin, kresoxim methyl, trifloxystrobin + tebuconazole, pyraclostrobin + metiram, flusilazole, tebuconazole, difenoconazole were evaluated. Carbendazim was included for comparision. In 2010, the weather was wet and humid during the 30 days of trial, favoring disease development and the percent disease index (PDI) values in untreated control reached 89.50. In all the fungicide treatments, the maximum PDI values were less than 6.63. The area under the disease progress curve (AUDPC) in untreated control was 837.31 but less than 100 in fungicide treatments. In 2011, PDI of anthracnose gradually increased from 0.00 to 40.44 (AUDPC 167.78) in untreated vines as the weather was not very conducive for development of anthracnose. The PDIs remained less than 2.56 in vines treated with fungicides (AUDPC less than 20.34) which were significantly lower than control. Bioassay studies indicated systemic acropetal and translaminar movement of azoxystrobin, kresoxim methyl and flusilazole in grape.